2019
DOI: 10.3892/mmr.2019.10748
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor pathway: Role, regulation and intervention in atherosclerosis therapy (Review)

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor originally isolated and characterized as the dioxin or xenobiotic receptor. With the discovery of endogenous ligands and studies of AhR knockout mice, AhR has been found to serve an important role in several biological processes, including immune responses and developmental and pathological regulation. In particular, it has been considered as a new major player in cardiovascular diseases. Recent studies have revealed that the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 93 publications
1
44
0
Order By: Relevance
“…The proposed mechanism for this increase was that transcription factor 21 (TCF21) could cooperate with AhR to activate inflammatory genes in SMCs that could contribute to coronary artery disease (CAD) [76]. Whilst this study suggests a deleterious role for AhR in the process of atherosclerosis, association studies investigating the relationships of AhR signalling with the risk and complications of atherosclerosis‐associated diseases are not conclusive [77]. Excitingly, recent evidence suggests that AhR can exert bidirectional effects on the regulation of inflammation, depending on the availability of external AhR ligands; in the absence of external ligands, AhR can mediate pro‐inflammatory effects [78].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism for this increase was that transcription factor 21 (TCF21) could cooperate with AhR to activate inflammatory genes in SMCs that could contribute to coronary artery disease (CAD) [76]. Whilst this study suggests a deleterious role for AhR in the process of atherosclerosis, association studies investigating the relationships of AhR signalling with the risk and complications of atherosclerosis‐associated diseases are not conclusive [77]. Excitingly, recent evidence suggests that AhR can exert bidirectional effects on the regulation of inflammation, depending on the availability of external AhR ligands; in the absence of external ligands, AhR can mediate pro‐inflammatory effects [78].…”
Section: Discussionmentioning
confidence: 99%
“…Research in the field of biomedicine has found that statins demonstrate good effects on lowering blood lipids and improving vascular endothelium. Lowering blood lipids mainly involves reducing cholesterol in serum, liver, and aorta, and lowering very low-density lipoprotein cholesterol (VLDL-C) and LDL-C, which can effectively prevent coronary heart disease and delay atherosclerosis (7)(8)(9). However, as few meta-analyses have been conducted on the effects of statins in the treatment of atherosclerosis, and there have been limitations in the existing studies such as small sample size and different research focuses, it is impossible to effectively judge the actual treatment effects of statins on atherosclerosis (10).…”
Section: Original Articlementioning
confidence: 99%
“…Activation of AhR may promote the development of AS through a series of inflammatory responses (Fardel, 2013; Lawal, 2017; Wu et al, 2011). A recent review presented the expression and regulatory roles of AhR in the development of AS, including inflammation, oxidative stress, and lipid infiltration (Zhu et al, 2019). However, the mechanism of AhR‐mediated atherogenesis is still unclear, and further exploration of downstream signaling pathways is needed.…”
Section: Underlying Mechanisms Of Pm25‐induced Asmentioning
confidence: 99%